Improved correction of VIPERS angular selection effects in clustering measurements. Issue Volume 11:Issue S308(2015) (12th October 2016) - Pezzotta, A.; Granett, B.R.; Bel, J.; Guzzo, L.; de la Torre, S.; ,
Abstract: Clustering estimates in galaxy redshift surveys need to account and correct for the way targets are selected from the general population, as to avoid biasing the measured values of cosmological parameters. The VIMOS Public Extragalactic Redshift Survey (VIPERS) is no exception to this, involving slit collisions and masking effects. Pushed by the increasing precision of the measurements, e.g. of the growth rate f, we have been re-assessing these effects in detail. We present here an improved correction for the two-point correlation function, capable to recover the amplitude of the monopole of the two-point correlation function ξ( r ) above 1 h -1 Mpc to better than 2.